The Role of Probiotics in Enhancing Immune Function in Preterm Low Birth Weight Infants (Eastern Medical College Journal, 2025)
Background: The establishment of complete enteral nutrition is a significant difficulty in the management of preterm low birth weight (LBW) infants. Probiotics are live microbial supplements that populate the gut with favorable flora, increase feeding tolerance, and encourage the expansion of these premises. The aim of the study is to observe probiotics’ activity in improving immunity in preterm, low birth weight neonates.Materials and methods: This randomized controlled clinical trial was carried out in the Department of Paediatrics, Abdul Malek Ukil Medical College & Jononeta Nurul Hoque Adhunik Hospital, Noakhali during January to December 2023. A total of 130 LBW infants were included in this study. Selected infants were randomly allocated to either probiotic groups (n=65) or control groups (n=65). Collected data were classified, edited, coded and entered into the computer for statistical analysis by using SPSS-23.Results: The average initiation of feeding was 4.3±1.0 days in the probiotics group and 4.5±0.9 days in the control group. Probiotics significantly decreased the time to full enteral feed and hospital stay compared to the control group. In the probiotics group, the mean duration of postnatal antibiotics was 9.89±2.6 days, while in the control group, it was 10.87±2.8 days. Ninety-six (96.72%) patients in the control group and 100% patients in the probiotics group had necrotizing enterocolitis stage II or lower. Five (5) patients (10%) in the control group and 3 (6%) in the probiotics group were found to be infected more than 3 days after birth.Conclusion: Probiotic supplementation in preterm low birth weight infants improves feed tolerance, decreases hospital stay, reduces the risk of infection and improves weight gain in comparison to non-supplement group.Eastern Med Coll J. July 2025; 10 (1): 23-28